2005
DOI: 10.3928/01913913-20051101-02
|View full text |Cite
|
Sign up to set email alerts
|

Acute Onset Concomitant Esotropia: Sensorial Evaluation, Prism Adaptation Test, and Surgery Planning

Abstract: Background and Objective: Acute acquired concomitant esotropia is a rare form of strabismus that usually presents during infancy or early childhood with diplopia and minimal refractive error. The aim of this study was to evaluate the response to the prism adaptation test in a group of normosensorial patients with acute acquired concomitant esotropia and to determine its predictive value for surgical outcome. Patients and Methods: Six patients (median ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“… 1 4 , 6 Some reports describe AACE as being an acute-onset condition confined to children ≥ 5 years of age, which might be one of the primary features that differentiates it from acquired nonaccommodative esotropia. 2 , 14 However, in several other studies it was reported that the acute deviation developed during infancy and early childhood 7 , 8 and diplopia was an inconsistent feature. 4 , 8 Here, we reviewed a large case series of AACE, and, the salient characteristics observed were: (1) concomitant nonaccommodative esotropia with acute onset, (2) an accompanying diplopia or visual confusion, (3) potential for normal binocular vision and highly favorable surgical outcomes for those with deviations >20 PD, (4) ≥ 5 years old at the time of onset, and (5) no tendency for spontaneous resolution.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 1 4 , 6 Some reports describe AACE as being an acute-onset condition confined to children ≥ 5 years of age, which might be one of the primary features that differentiates it from acquired nonaccommodative esotropia. 2 , 14 However, in several other studies it was reported that the acute deviation developed during infancy and early childhood 7 , 8 and diplopia was an inconsistent feature. 4 , 8 Here, we reviewed a large case series of AACE, and, the salient characteristics observed were: (1) concomitant nonaccommodative esotropia with acute onset, (2) an accompanying diplopia or visual confusion, (3) potential for normal binocular vision and highly favorable surgical outcomes for those with deviations >20 PD, (4) ≥ 5 years old at the time of onset, and (5) no tendency for spontaneous resolution.…”
Section: Discussionmentioning
confidence: 96%
“… 5 AACE is characterized by a sudden onset of concomitant esotropia with diplopia. 1 3 , 6 , 7 In 1958, Burian and Miller reported 5 cases of AACE and described the 3 categorical features of AACE, which have been accepted as the fundamental symptoms and the pivotal work in this area. 1 Since then, findings from a number of reports have added to this work.…”
Section: Introductionmentioning
confidence: 99%
“…AACE is believed to occur during infancy or early childhood, [ 14 ] but some studies found that it can occur in older children and adults. [ 5 , 11 , 14 , 15 ] Accordingly, in the present study, the age at esotropia onset ranged from 3 to 62 years, with a mean age (± SD) of 23.1 ± 11.7 years. Six cases (8.7%) presented at < 10 years, 23 cases (33.3%) presented at 10 to 18 years, and 40 cases (58.0%) presented at >18 years.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons may be related to the prism-eating phenomenon caused by mechanisms that compensate for the deviation. Application of the prism adaptation test (PAT) signi cantly improved the success rate of surgery in AACE patients [6][7][8] However, the PAT itself requires a long time, especially for patients with high strabismus angles. It is di cult for these patients to wear prisms for several days.…”
Section: Discussionmentioning
confidence: 99%
“…Extraocular muscle surgery remains the main treatment method. However, because of the "eating-prism phenomenon", it is di cult to accurately correct the target deviation [6][7][8][9][10]. Many authors have published satisfactory results in the treatment of various types of strabismus in children, including AACE, with botulinum toxin [1,2,9,[11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%